FUNGSI KETERANGAN DALAM KALIMAT MAJEMUK BERTINGKAT DALAM KOMPAS MINGGU - YANTI, TRULI ANJAR (Educatio Vitae, 2014)
This study analysis the functions of adverbs in compound sentences inKompas Minggu. Compound sentence is a combination of two or more sentenceswhich the position and relation are equal or unequal.This researrch is qualitative research becouse it describes the data in thefrom Kompas Minggu from April to June 2013.Based on the result of the study the type of main clause-subordinate clauseconsists of 12 patterns, they are as follows (1) S-P-Adv, (2) S-P-O-Adv, (3) S-PPel-Adv, (4) S-P-O-Pel-Adv, (5) S-P-Adv-Adv, (6) S-P-O-Adv-Adv, (7) S-PComp-Adv-Adv, (8) S-Adv-P-Adv, (9) P-S-Adv, (10) P-Adv-S-Adv, (11) P-Adv,dan(12) P-S-Comp-Adv. Furthemore, subordinate clause-main clause consists of11 patterns, they are (1) Adv-S-P, (2) Adv-S-P-O, (3) Adv-S-P-Comp, (4) Adv-SP-O-Comp,(5) Adv-S-P-Comp, (6) Adv-S-Adv-P, (7) Adv-S-P-O-Adv, (8) Adv-P, (9) Adv-P-S, (10) Adv-P-S-Comp, dan (11) Adv-P-O.Function of adverbs in subordinate clauses there are 17 patterns they are asfollows (1) Conj-S-P, (2) Conj-P, (3) Conj-P-O, (4) Conj-P-S, (5) Conj-P-Adv,(6) Conj-S-P-O, (7) Conj-S-P-Adv, (8) Conj-P-Comp, (9) Conj-S-P-Comp, (10)Conj-S-P-O-Adv, (11) Conj-P-O-Adv, (12) Conj-S-Adv-P, dan (13) Conj-SComp.While the types of adverb used in compound sentences are of 12 typesnamely (1) adverb of time, (2) adverb of purpose, (3) adverb of effect, (4) adverbof couse, (6) adverb of manner, (7) adverb of condition, (7) adverb of exception,(8) adverb of means, (9) adverb of comparison, (10) adverb of result, (11)certainty, and (12) adverb of modifier.